1994
DOI: 10.1103/physrevb.49.9336
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the amorphization of α-quartz under pressure

Abstract: Extensive molecular-dynamics simulations have been performed within a classical force-field model for the pressure-induced amorphization of quartz. In agreement with earlier molecular-dynamics studies, we find that a phase transition occurs within the experimental pressure range of the amorphization transformation. However, at variance with previous interpretations, we find that the resulting phase is not amorphous. The correlation functions of the equilibrated structure can be shown to be consistent with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The structure obtained at this pressure appears to be quite similar to the structure calculated for SiO 2 at 21.5 GP a [112]. Furthermore it is shown that α-quartz-like GeO 2 close to the transition is mechanically unstable as some of the elastic moduli of the lattice become negative.…”
Section: Force Field Parameterssupporting
confidence: 72%
“…The structure obtained at this pressure appears to be quite similar to the structure calculated for SiO 2 at 21.5 GP a [112]. Furthermore it is shown that α-quartz-like GeO 2 close to the transition is mechanically unstable as some of the elastic moduli of the lattice become negative.…”
Section: Force Field Parameterssupporting
confidence: 72%
“…There is a noticeable separation in the M − µ diagram between galaxies of different morphological types. It was suggested by Binggeli (1994) that the M − µ diagram for stellar systems might be the equivalent of the HR diagram for stars (see Fig. 1 of his review).…”
Section: Discussion Of Results and Conclusionmentioning
confidence: 99%
“…The BBD showing the natural morphological segregation of Virgo cluster galaxies in the space mapped by central surface brightness and absolute magnitude has been shown by several authors (Caldwell 1983;Binggeli, Sandage, & Tarenghi 1984;Kormendy 1985;Binggeli 1994). From these seminal works, in Binggeli's words, "The M − µ diagram for stellar systems might well become the equivalent of the HR diagram for stars".…”
Section: The Bivariate Brightness Distribution: a Comparison With Litmentioning
confidence: 99%